Brain neurochemistry in unmedicated obsessive–compulsive disorder patients and effects of 12‐week escitalopram treatment: 1H‐magnetic resonance spectroscopy study. Issue 7 (23rd May 2019) - Parmar, Arpit; Sharan, Pratap; Khandelwal, Sudhir Kumar; Agarwal, Khushbu; Sharma, Uma; Jagannathan, Naranamanglam Raghunathan
Abstract : Aim: The purpose of this study was to examine treatment‐related neurochemical changes in 28 unmedicated obsessive–compulsive disorder (OCD) patients using 1 H‐magnetic resonance spectroscopy ( 1 H‐MRS). Methods: We included subjects diagnosed with OCD ( n = 28), each with a total duration of illness of less than 5 years, as a study group and age‐ and sex‐matched healthy controls ( n = 26). The inclusion criteria for the OCD group were right‐handed individuals aged 18 years or older who had not been on any specific treatment for OCD for the last at least 8 weeks and who had no other psychiatric comorbidity. A pre–post and case–control design was employed in which OCD patients underwent 1 H‐MRS at baseline and 12 weeks after treatment with escitalopram ( n = 21). Clinical assessment was carried out using a semi‐structured pro forma Yale–Brown Obsessive Compulsive Scale and the World Health Organization Disability Assessment Scale 2.0 before and after treatment. Volume‐localized 1 H‐MRS was carried out with a 3‐Tesla Philips MR scanner. Results: Our data suggested higher levels of myoinositol (mI), total choline (tCho), and glutamate+glutamine (Glx) in the medial thalamus at pre‐assessment in OCD subjects as compared to healthy controls and a significant reduction in tCho and Glx after treatment in OCD subjects. The mI levels in the caudate nucleus and Glx levels in the anterior cingulate cortex were significantly correlated with disease severity on the Yale–Brown Obsessive Compulsive Scale. Conclusion: Our study supports the hypothesis of a hyper‐glutaminergic state (as suggested by increased Glx levels) and neurodegeneration (as suggested by increased tCho and mI in the thalamus) in cortico‐striato‐thalamocortical circuitry in OCD patients as suggested by previous studies using MRS as well as other functional imaging studies.